Determinant of the level of sharia compliance of Islamic banks in Indonesia - Muhammad Adib Hasani; Rifqi Muhammad (Journal of Contemporary Accounting, 2022)
This study aims to examine the relationship between SSB remuneration, SSB cross-membership, board independence, audit committee independence, IAH, leverage, profitability, and firm size to the level of sharia compliance of Islamic banks. In this study, sharia compliance is measured by an index compiled in previous studies. The sample used in this study is 10 Islamic banks that have published annual reports on each website with an observation period between 2015-2020. Multiple regression analysis using EViews 10 application. The results of this study indicate that board independence, audit committee independence, firm size, and SSB cross-membership significantly affect sharia compliance. While SSB remuneration, IAH, leverage, and profitability do not affect the level of sharia compliance.